How the Linker Connecting the Two Kringles Influences Activation and Conformational Plasticity of Prothrombin - Pozzi, Nicola (J Biol Chem, 2016)
A flexible linker (Lnk2) composed of 26 amino acids connects kringle-1 to kringle-2 in the coagulation factor prothrombin. Recent studies point to Lnk2 as a key determinant of the structure and function of this zymogen. Using a combination of mutagenesis, structural biology, and single molecule spectroscopy, we show how Lnk2 influences activation and conformational plasticity of prothrombin. Scrambling the sequence of Lnk2 is inconsequential on activation, and so is extension by as many as 22 residues. On the other hand, below a critical length of 15 residues, the rate of prothrombin activation increases (10-fold) in the absence of cofactor Va and decreases (3-fold) in the presence of cofactor. Furthermore, activation by prothrombinase takes place without preference along the prethrombin-2 (cleavage at Arg(271) first) or meizothrombin (cleavage at Arg(320) first) pathways. Notably, these transitions in the rate and pathway of activation require the presence of phospholipids, pointing to an important physiological role for Lnk2 when prothrombin is anchored to the membrane. Two new crystal structures of prothrombin lacking 22 (ProTΔ146–167) or 14 (ProTΔ154–167) residues of Lnk2 document striking conformational rearrangements of domains located across this linker. FRET measurements of freely diffusing single molecules prove that these structural transitions are genuine properties of the zymogen in solution. These findings support a molecular model of prothrombin activation where Lnk2 presents the sites of cleavage at Arg(271) and Arg(320) to factor Xa in different orientations by pivoting the C-terminal kringle-2/protease domain pair on the N-terminal Gla domain/kringle-1 pair anchored to the membrane.